2020
DOI: 10.1088/1757-899x/943/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of magnesium oxide nanoparticles using Aloe barbadensis leaf latex extract

Abstract: Biological methods are employed to yield less or non-toxic MgO nanoparticles to utilize them in biological applications. Among various biosynthesis approaches, plant extracts with phytochemicals, especially from leaves, are widely used to fabricate MgO nanoparticles, due to their high availability, rapid synthesis and ability to yield smaller stable nanoparticles. Aloe barbadensis is a succulent xerophytic plant with unique characteristics to withhold water in its leaf named parenchymal gel, which is protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The total weight loss of the CuO-NPs was recorded as 63% until 600 • C, while NiO-NPs resulted in only 69% weight loss, and the hybrid NPs total loss was observed as 59.3%. The initial weight loss up to 150 • C is attributed to the dehydration and loss of moisture content from the samples [54]. Our results thus indicated that biosynthesized hybrid are thermally more stable than NiO-NPs, and NiO-NPs are more stable than CuO-NPs.…”
Section: Thermal Propertiesmentioning
confidence: 69%
“…The total weight loss of the CuO-NPs was recorded as 63% until 600 • C, while NiO-NPs resulted in only 69% weight loss, and the hybrid NPs total loss was observed as 59.3%. The initial weight loss up to 150 • C is attributed to the dehydration and loss of moisture content from the samples [54]. Our results thus indicated that biosynthesized hybrid are thermally more stable than NiO-NPs, and NiO-NPs are more stable than CuO-NPs.…”
Section: Thermal Propertiesmentioning
confidence: 69%
“…36 The biosynthesis approach helps to reduce environmental toxicity by eliminating toxic byproducts and potential toxicity to living organisms, such as humans, animals, and plants, compared with conventional chemically and physically synthesized nanoparticles. 278 The surface functional groups, size, and shape of nanoparticles play key roles in their eco-friendly nature. 170,279 It should be noted that the biochemicals and biomolecules present on the surface of biosynthesized nanoparticles are less/nontoxic as they are biogenic compared with physically/chemically synthesized nanoparticles.…”
Section: Innovative Opportunities In Green Nanoscience and Nanotechno...mentioning
confidence: 99%
“…Titanium dioxide nanoparticles were minimised and manufactured using an Aloe leaf extract in aqueous solution (TiO 2 nanoparticles). The biosynthesis of 2 Adsorption Science & Technology TiO 2 NPs was confirmed by UV-vis spectroscopy [26].…”
Section: Introductionmentioning
confidence: 97%
“…Titanium dioxide nanoparticles were minimised and manufactured using an Aloe leaf extract in aqueous solution (TiO 2 nanoparticles). The biosynthesis of TiO 2 NPs was confirmed by UV-vis spectroscopy [26]. When combined with smaller MgO nanoparticles, as shown by HRTEM and FESEM study, Aloe barbadensis phytochemical extract may be employed for a variety of biological and biomedical applications [27, 28].…”
Section: Introductionmentioning
confidence: 99%